Neighborhood Characteristics and Colorectal Cancer Survivors' Quality of Care - Ulrike Boehmer; Jennifer Potter; Melissa A. Clark; Al Ozonoff; Rachel M. Ceballos; Michael Winter; Kevan L. Hartshorn (Mary Ann Liebert, 2019)
Purpose: Quality cancer care entails receipt of a Survivorship Care Plan (SCP). The purpose of this study was to determine differences in SCP delivery by patient-level and neighborhood characteristics. Methods: We obtained California cancer registry data on individuals who were diagnosed with stage I, II, or III colorectal cancer (CRC) between 2012 and 2015 and resided in predetermined geographic areas. We then mailed them a questionnaire, which queried about receipt of a SCP and its content. SCP was defined by content, as summary of cancer treatment, cancer surveillance recommendations, and/or an individualized preventive care. Using logistic regression modeling, each measure of SCP, as well as the summary measure (none vs. any), was evaluated by person-level characteristics. Subsequently, neighborhood-level characteristics were added to the model to explore their additional value. Results: Overall 80% of CRC survivors received a SCP. Receipt of SCPs was associated with person-level characteristics, while neighborhood characteristics did not make an additional contribution. Young, male employed survivors and those with more recent diagnoses or later cancer stages had greater odds of receiving a SCP. Conclusion: When providing SCPs, health care providers prioritize patient groups who they may perceive as vulnerable or likely to benefit from SCPs.